2017
DOI: 10.2196/medinform.7400
|View full text |Cite
|
Sign up to set email alerts
|

Is There Evidence of Cost Benefits of Electronic Medical Records, Standards, or Interoperability in Hospital Information Systems? Overview of Systematic Reviews

Abstract: BackgroundElectronic health (eHealth) interventions may improve the quality of care by providing timely, accessible information about one patient or an entire population. Electronic patient care information forms the nucleus of computerized health information systems. However, interoperability among systems depends on the adoption of information standards. Additionally, investing in technology systems requires cost-effectiveness studies to ensure the sustainability of processes for stakeholders.ObjectiveThe ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…Most of them conclude that the quality of the included studies was poor to moderate, reported outcomes were often heterogeneous, and the generalizability of the results therefore very limited [e.g. 1,4,21,62,74,76,110,111,146]. So, while many of these systematic reviews reach further back in time than this study, it can be concluded, in the light of the present assessment of literature, that this basic problem has not changed in recent years.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Most of them conclude that the quality of the included studies was poor to moderate, reported outcomes were often heterogeneous, and the generalizability of the results therefore very limited [e.g. 1,4,21,62,74,76,110,111,146]. So, while many of these systematic reviews reach further back in time than this study, it can be concluded, in the light of the present assessment of literature, that this basic problem has not changed in recent years.…”
Section: Discussionmentioning
confidence: 71%
“…These ndings are broadly con rmed by an overview of systematic reviews on EMR/EHR by Reis et al [21] rare -so they conclude that proof of clinical improvements and economic effectiveness is lacking [40,41].…”
Section: Electronic Health Records/electronic Medical Records (Ehr/emr)mentioning
confidence: 79%
See 1 more Smart Citation
“…Another important result of this work was the measurement of data quality metrics to gauge the impact of the eHealth-Interop platform in informational continuity of care, since impact of HIE are yet inadequately studied [44,45].…”
Section: Principal Resultsmentioning
confidence: 99%
“…Numerous basic clinical informatics research questions remain to be satisfactorily addressed,27 including in the fields of: Cost effectiveness28 , 29Efficiency/productivity30 – 32Impact on service utilisation33Patient empowerment/outcomes34Decision support35Usability and human factors36 , 37Unintended consequences3841Application of safety-critical software engineering methods 42…”
Section: Expanding Clinical Informatics Research and Education Capacimentioning
confidence: 99%